The Paradigmatic and Syntagmatic Priming Effect of Part of Speech Representation. (6th June 2022) - Xue, Carol Lin
Abstract : Part of speech feature is the representation between syntactic morphology and semantic category. Priming effect experiment can test the correlation between the parts of speech feature and the lexical processing process. This article puts forward part of speech representation paradigmatic and syntagmatic effect hypotheses. The experiments applied the design pattern of 3 (part of speech: noun by predicate by nonword) ∗ 2 (interval time: 50 by 500 milliseconds) ∗ 3 (English level: elementary by intermediate by advanced). Subjects are requested to make options of the part of speech of the target words. This study shows that when Chinese English learners extract an individual word, their choices are still influenced by part of speech factor without the restrictions of constructive syntagmatic semantic conditions. Both the syntagmatic and paradigmatic effects are verified. Part of speech priming effect intensity is influenced by the English acquisition levels of the subjects.